Are Medical Professionals prone to suicide? - Dr. Devraj Ramakrishnan (International Journal of Medical Science And Diagnosis Research, 2018)
Medical schools are known to be stressful environments for students and hence medical students have been believed to experience greater incidences of depression than others. Global prevalence of depression among medical students was found to be 28% and suicidal ideation in the last year was 11.1%. The medical students often lack the competence or aptitude to meet the tough demands of people. Incidences of doctors being blamed and brutally attacked when a patient dies or is seriously ill is increasing in our country day by day Top Academic factors for stress and suicidal ideation included academic curriculum, dissatisfaction with class lectures, lack of time for recreation, performance in examination, lack of special guidance from faculty and high parental expectations Other stressors included personal (female gender, break-up in relationships, demise of spouse or children), financial (education loan), health (cancer and depression), and occupational (physical and psychological hazards like work place harassment) problems; ideation was more likely with multiple stressors. This review aids the stakeholders to take necessary measures to reduce depression and suicidal ideation among doctors. Preventing suicide still seems to be a distant dream, but efforts to reduce suicide rates should be taken at individual, societal and organization levels. Keywords: Suicide, Medical Professionals, Stress, Depression